1998
DOI: 10.1034/j.1399-3054.1998.1020201.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture on sugar medium enhances photosynthetic capacity and high light resistance of plantlets grown in vitro

Abstract: The significance of photosynthetic photon flux (PPF) and sugar feeding for the production of plants in vitro is only poorly understood. Nicotiana tabacum L. plantlets were grown photoautotrophically and photomixotrophically (3% sucrose) at two different PPFs (60 µmol m−2 s−1 and 200 µmol m−2 s−1) to investigate the effect of these culture parameters on photosynthetic performance and growth. Photomixotrophically‐grown plantlets showed an increase in carbohydrate content, mainly in glucose and fructose. Plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 0 publications
5
30
0
1
Order By: Relevance
“…For the PFD levels tested (18 and 43 μmol m -2 s -1 ), no difference between dry matter averages (11.9 mg per plant and 13.6 mg per plant, respectively) was obtained. However, Tichá et al (1998) observed a positive effect in biomass and leaf area of Nicotiana tabacum plants with addition of 30 g L -1 sucrose in the culture medium and Galzy and Compan (1992) obtained similar results with Vitis rupestris. The smallest dry matter of the aerial part (5.0 mg per plant) was obtained when sucrose was absent from the culture medium, probably due the necessity of increasing not only the PFD but in vitro CO 2 enrichment and humidity in the culture tubes environment in order to promote photosynthesis, transpiration and accumulation of dry matter (Kozai and Nguyen, 2003).…”
Section: Resultssupporting
confidence: 52%
“…For the PFD levels tested (18 and 43 μmol m -2 s -1 ), no difference between dry matter averages (11.9 mg per plant and 13.6 mg per plant, respectively) was obtained. However, Tichá et al (1998) observed a positive effect in biomass and leaf area of Nicotiana tabacum plants with addition of 30 g L -1 sucrose in the culture medium and Galzy and Compan (1992) obtained similar results with Vitis rupestris. The smallest dry matter of the aerial part (5.0 mg per plant) was obtained when sucrose was absent from the culture medium, probably due the necessity of increasing not only the PFD but in vitro CO 2 enrichment and humidity in the culture tubes environment in order to promote photosynthesis, transpiration and accumulation of dry matter (Kozai and Nguyen, 2003).…”
Section: Resultssupporting
confidence: 52%
“…Pruski et al (2000) found also yellow basal leaves in Prunus virginiana L. under cold storage both in dark and light conditions ascribing it to the presence of sucrose in the storage media. The presence of exogenous sugars is thought to limit the photosynthesis by several works in many species (Hdider, Desjardins 1994;Van Huylenbroech, Debergh 1996;Tichá et al 1998;Rybczynski et al 2007;Yuanyuan et al 2009) according to Koch's theory (Koch 1996) on the inhibitory influence of sugars on photosynthesis. We detected that the presence of PGRs seems to improve the quality of leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence parameters characterising either dark-adapted state or light-adapted state were calculated according to the following formulae: maximum quantum yield of PSII, ΦPSII = Fv/Fm = (Fm -Fo)/Fm; actual rate of photochemical reduction of RC PSII, Qr/Qt = (Fs -Fo)/(Fm' -Fo) and Stern-Volmer definition of non-photochemical quenching, NPQ = (Fm -Fm')/ Fm' according to Roháček (2002). For more details see, e.g., Tichá et al (1998).…”
Section: Chlorophyll a Fluorescencementioning
confidence: 99%